Natural Killer Response and Lipo-Metabolic Profile in Adults with Low HDL-Cholesterol and Mild Hypercholesterolemia: Beneficial Effects of Artichoke Leaf Extract Supplementation. (6th January 2019) - Rondanelli, M.; Castellazzi, A. M.; Riva, A.; Allegrini, P.; Faliva, M. A.; Peroni, G.; Naso, M.; Nichetti, M.; Tagliacarne, C.; Valsecchi, C.; Fazia, T.; Perna, S.; et al.
Abstract : The aim of the present study is to evaluate the effects of 60-day artichoke leaf extract (ALE) supplementation (250mg, twice daily) on cytokines levels, natural killer cell (NK) response, and lipo-metabolic profile (HDL, LDL, and total-cholesterol, triglycerides (TG), ApoB, ApoA, lipid accumulation product (LAP), glucose, insulin, and homeostasis model assessment of insulin resistance (HOMA-IR)) in twenty adults (9/11 males/females, age=49.10 ± 13.74 years, and BMI=33.12 ± 5.14 kg/m 2 ) with low HDL-C and mild hypercholesterolemia. Hierarchical generalized linear model, adjusted for sex, BMI, and age, has been used to evaluate pre-post treatment changes. A significant increase for HDL-C ( β =0.14, p=0.0008) and MCP-1 ( β =144.77, p=0.004) and a significant decrease for ApoB/ApoA ( β =-0.07, p=0.03), total-C/HDL-C ratio ( β =-0.58, p<0.001), and NK response at stimulus low ( β =0.43, p=0.04), medium ( β =0.40, p<0.001), and high ( β =0.42, p=0.001) have been found. These results support the benefits of ALE supplementation on metabolic profile.